2006
DOI: 10.1111/j.1439-0442.2006.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seasonal and Physiological Variations on the Serum Chemistry, Vitamins and Thyroid Hormone Concentrations in Sheep

Abstract: The aim of this study was to investigate the possible effects of the reproductive status and seasonal variations on the serum chemistry and vitamin status and their relationships with the thyroid hormones in Sakiz-Awassi crossbreed sheep. The sheep (n = 34) were divided into two groups. The first group (n = 22) was mated; the second group (n = 12) was not mated. Their serum samples were collected four times a year at the each season and under reproductive status. The periods are 1, early pregnancy (October); 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
76
4
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 21 publications
12
76
4
4
Order By: Relevance
“…The seasonal pattern of blood TH levels often showed maximal values during winter (cold months) and minimal during summer (hot months) (Salem et al, 1991;Webster et al, 1991;Okab et al, 1993;Menegatos et al, 2006). However, contrasting results have been reported (Kloren et al, 1993;Rhind et al, 1998; Ashutosh et al, 2001;Yokus et al, 2006). In the Sahel desert, plasma T3 and T4 levels did not change significantly from the beginning of the cool season (December) until the end of the dry warm season (May), but a highly significant rise of both hormones was observed at the onset of the humid warm season (June) (Assane and Sere, 1990).…”
Section: Season Effectsmentioning
confidence: 99%
“…The seasonal pattern of blood TH levels often showed maximal values during winter (cold months) and minimal during summer (hot months) (Salem et al, 1991;Webster et al, 1991;Okab et al, 1993;Menegatos et al, 2006). However, contrasting results have been reported (Kloren et al, 1993;Rhind et al, 1998; Ashutosh et al, 2001;Yokus et al, 2006). In the Sahel desert, plasma T3 and T4 levels did not change significantly from the beginning of the cool season (December) until the end of the dry warm season (May), but a highly significant rise of both hormones was observed at the onset of the humid warm season (June) (Assane and Sere, 1990).…”
Section: Season Effectsmentioning
confidence: 99%
“…They are useful in diagnosing diseases and determining their prognosis, as well as in preventive programs. Comparison of biochemical results and physiological ranges is complex, because values depend on many factors, such as: breed, sex, age, nutrition, physiological conditions (pregnancy and lactation), illness and seasonal variations (YOKUS et al, 2006). Using reference intervals available from textbooks (KANEKO et al, 2008) has been shown to be inappropriate considering the large number (much more than the expected 5%) of clinically healthy animals falling outside the published intervals (VOJTA et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have not found seasonal variations in other ruminants such as sheep [16] or white-tailed deer (Odocoileus virginianus; [17]). In contrast, DelGuidice et al [18] described seasonal variations in total protein that are similar to the pattern observed in our study.…”
Section: Discussionmentioning
confidence: 99%